THE CHURCH AS GOD’S FAMILY: AN AFRICAN MODEL OF SYNODALITY (Hekima Review, 2023)
In line with Avery Dulles’ theory of the varieties of “models of the Church,” each imperfect and complementary to other models, this paper presents the Church as God’s family and a model of a synodal Church. From the sacredness and importance of family in Africa, I argue that this model, as an antidote to clericalism, particularism, and ethnocentrism, is a better expression of the Church. As God’s family, the Church is characterized by the participation of all, mutual listening, the principle of subsidiarity, discernment in common, and walking together as people of God. From this African perspective, the Church, viewed as God’s family, offers a concrete and fruitful seedbearing model for the experience of Synodality.